Unravelling the systematics of Nodularia (Bivalvia, Unionidae) species from eastern Russia. Issue 3 (3rd April 2018) - Klishko, Olga K.; Lopes-Lima, Manuel; Froufe, Elsa; Bogan, Arthur E.; Abakumova, Vera Y.
Abstract : Conservation efforts have been hindered by data deficient conservation status assessments, especially due to taxonomic problems. This is especially true for many eastern Russian species of freshwater mussels, where distinct classification systems have complicated their delimitation and identification. Nodularia is a widespread eastern Asian freshwater mussel genus, present from Vietnam in the south to the Magadan region in eastern Russia in the north. The number of recognized species in the genus Nodularia in eastern Russia has been inflated over the last several decades due to the use of a typological species concept, the so-called 'Comparatory Method'. This method uses a single diagnostic character for species delimitation, i.e., the arc of maximal convexity of the shell's outline. Using this classification system, 10 species were recognized for far eastern Russia under the genus Nodularia Conrad, 1853, divided into three subgenera: Nodularia s. str., Amurunio and Magadaninaia . Since it is not supported by any other classification methods, the current comparatory classification is rejected by many Russian and international scientists, who only recognize a single species for that region, i.e., Nodularia douglasiae . Therefore, the aim of the present study is to clarify the taxonomy and systematics of the Nodularia genus in far eastern Russia and adjacent territories, using a multiple dataset approach that combines distribution with detailed conchological and anatomical analyses with morphometry and COI barcoding molecular techniques. All analyses performed in this study support the existence of a single Nodularia species in eastern Russia, i.e., N. douglasiae .